Transforming business education: the impact of virtual reality on learning outcomes in case studies - Hubbard, Timothy D. (Frontiers in Virtual Reality, 2025)
There is a critical gap in educational research in understanding the effectiveness of written, video, and virtual reality (VR) business cases for instructional purposes. The case method is fundamental in business education, with traditional written cases predominating, though video cases are increasingly popular. Recently, VR business cases have been proposed for their potential benefits, yet evidence comparing their effectiveness is limited. This study examines learning outcomes of undergraduate business students using written, video, and VR business case study media. To my knowledge, this is among the first studies to empirically examine the specific trade-offs associated with adopting VR compared to traditional business case-study presentations. In the study, students were randomly assigned to a medium and completed a survey assessing their experiences, recollection, and engagement. Results show that VR enhances presence but increases cognitive load compared to written and video presentations. VR cases improve visual information recall but reduce numerical fact recall and interest in adopting VR as an educational tool. These findings suggest that while VR enhances visual engagement, it introduces higher task demands and is not universally preferred. This dual impact highlights the need for careful integration of VR in business curricula, especially where visual context is crucial. The study’s conclusions provide novel insights into the unique advantages and challenges of VR, significantly advancing our understanding of how emerging technologies impact student engagement and learning outcomes.